Influences on student motivation and independent learning skills: cross-cultural differences between Hong Kong and the United Kingdom - Lo, Noble Po-kan; Bremner, Pauline A. M.; Forbes-McKay, Katrina E. (Frontiers in Education, 2024)
Introduction This study examined the ways in which different influences on student motivation and the development of independent learning (IL) skills might be constituted across students learning within different educational cultures. Previous studies on student motivation and IL have suggested the potential for differing conceptualizations of IL and its strategies (ILS), prompting questions as to the sources of these distinctions. One theory is that they might be influenced by differing cultural constructions of these concepts or may be linked to different motivations with respect to the purposes and outcomes of education. Methods This study addressed a research gap with respect to these differences in the British and Chinese contexts by examining the responses of students sampled from a university in Scotland and a university in Hong Kong. Through mixed-methods research comprising quantitative analysis of questionnaires and thematic analysis of interview data, this research project compared conceptualizations of IL and ILS across both these contexts and highlighted the role that student motivation might play in either context. Results The analytical results showed differences in the conception of IL and the implementation of ILS potentially due to differing cultural contexts. Discussion Further cross-cultural comparative research is needed with a study design that excludes the influence of institutional and demographic factors to better isolate the influence of culture on perception of IL and use of ILS.